2000
DOI: 10.1054/bjoc.2000.1315
|View full text |Cite
|
Sign up to set email alerts
|

Anti-GnRH antibodies can induce castrate levels of testosterone in patients with advanced prostate cancer

Abstract: D17DT consists of the GnRH decapeptide linked to diphtheria toxoid. The aim of this pilot study was to assess the tolerance of D17DT and the production of anti-GnRH antibodies from two doses, 30 and 100 μg, in patients with locally advanced prostate cancer. Twelve patients with histologically proven prostate cancer in whom hormonal therapy was indicated were recruited. Patients received either 30 or 100 μg given intramuscularly on three separate occasions over six weeks. Patients were followed up and blood was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 11 publications
(9 reference statements)
1
37
1
Order By: Relevance
“…Titers were only slightly increased in two stallions, while two other stallions responded with substantial antibody titers. Such a large variation in antibody responses after GnRH immunization is shown in the majority of the GnRHimmunization studies in which sexually mature subjects are involved (Chappel et al, 1980;Lincoln et al, 1982;Schanbacher et al, 1983;Grizzle et al, 1987;Simms et al, 2000;Malmgren et al, 2001). Several factors may affect the immunogenicity of the applied vaccines, such as the type and amount of antigen, the adjuvant, vaccination schedule and the species involved.…”
Section: Discussionmentioning
confidence: 99%
“…Titers were only slightly increased in two stallions, while two other stallions responded with substantial antibody titers. Such a large variation in antibody responses after GnRH immunization is shown in the majority of the GnRHimmunization studies in which sexually mature subjects are involved (Chappel et al, 1980;Lincoln et al, 1982;Schanbacher et al, 1983;Grizzle et al, 1987;Simms et al, 2000;Malmgren et al, 2001). Several factors may affect the immunogenicity of the applied vaccines, such as the type and amount of antigen, the adjuvant, vaccination schedule and the species involved.…”
Section: Discussionmentioning
confidence: 99%
“…We did not specifically address the duration of the immune response, but various reports evidently show that immune responses raised against endogenous antigens are fully reversible (38)(39)(40)(41)(42). Long-term data with a peptide-based GnRH-targeting cancer vaccine for testosterone deprivation, also developed by us (43), showed that testosterone levels reappeared ∼30 wk later (43), showing that anti-GnRH immunity is indeed reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Suppression of testosterone via an anti-LHRH response leads to a reduction in dihydrotestosterone and indirectly controls prostatic hyperplasia. A related application for anti-LHRH vaccines in men is for treatment of prostatic cancer, and a number of phase I/II studies have shown some degree of efficacy in men with this tumor (168).…”
Section: Vaccines Against Reproductive Hormonesmentioning
confidence: 99%